2021
DOI: 10.1017/neu.2021.14
|View full text |Cite
|
Sign up to set email alerts
|

Effect of transcranial direct current stimulation on in-vivo assessed neuro-metabolites through magnetic resonance spectroscopy: a systematic review

Abstract: Objective: Previous studies have examined the effect of transcranial direct current stimulation (tDCS) on the in-vivo concentrations of neuro-metabolites assessed through magnetic resonance spectroscopy (MRS) in neurological and psychiatry disorders. This review aims to systematically evaluate the data on the effect of tDCS on MRS findings and thereby attempt to understand the potential mechanism of tDCS on neuro-metabolites. Methods: The relevant literature was obtained through PubMed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…The spatial specificity of this effect also aligns well with the hypothesized mechanism of action of atDCS on the behavioral measures (see above). In fact, there is evidence indicating that tDCS modulates neuro-metabolite levels at the site of stimulation and that this translates into alterations in behavioral outcomes ( Chhabra et al, 2021 ). Notably, the “online” obtained effect on encoding processes is in accordance with the HERA (Hemispheric Encoding Retrieval Asymmetry) model, which postulates that the left DLPFC is crucially involved in the encoding of memory contents, whereas the right DLPFC is crucial for retrieval ( Tulving et al, 1994 ; Nyberg et al, 1996 ; Habib et al, 2003 ; Manenti et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…The spatial specificity of this effect also aligns well with the hypothesized mechanism of action of atDCS on the behavioral measures (see above). In fact, there is evidence indicating that tDCS modulates neuro-metabolite levels at the site of stimulation and that this translates into alterations in behavioral outcomes ( Chhabra et al, 2021 ). Notably, the “online” obtained effect on encoding processes is in accordance with the HERA (Hemispheric Encoding Retrieval Asymmetry) model, which postulates that the left DLPFC is crucially involved in the encoding of memory contents, whereas the right DLPFC is crucial for retrieval ( Tulving et al, 1994 ; Nyberg et al, 1996 ; Habib et al, 2003 ; Manenti et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…In human studies using magnetic resonance spectroscopy, it was found that tDCS alters the levels of multiple neuro-metabolites, particularly glutamate and GABA, specifically but not limited to the site of stimulation (see Chhabra et al, 2021 for a review). In both young and older healthy adults and in patients with neurological and psychiatry disorders, main results confirmed that anodal tDCS induces a reduction in GABA levels (Stagg et al, 2009 ; Kim et al, 2014 ; Bachtiar et al, 2015 ; Antonenko et al, 2017 ), while cathodal tDCS led to a reduction of glutamate levels (Stagg et al, 2009 ).…”
Section: Potential Effects Of Tdcs On Plasticity and Neuronal Transmi...mentioning
confidence: 99%
“…In both young and older healthy adults and in patients with neurological and psychiatry disorders, main results confirmed that anodal tDCS induces a reduction in GABA levels (Stagg et al, 2009 ; Kim et al, 2014 ; Bachtiar et al, 2015 ; Antonenko et al, 2017 ), while cathodal tDCS led to a reduction of glutamate levels (Stagg et al, 2009 ). However, the baseline level of the neuro-metabolites may predict the outcome after tDCS, as well as the number of stimulation sessions (Chhabra et al, 2021 ).…”
Section: Potential Effects Of Tdcs On Plasticity and Neuronal Transmi...mentioning
confidence: 99%
“…tDCS is a noninvasive, portable, safe, and painless method of brain stimulation, which works by changing cortical excitability and functional connectivity between brain regions (Nitsche & Paulus, 2000; Sellaro et al, 2016). The therapeutic mechanism of tDCS is related to polarity‐dependent neurophysiological changes induced by the target cortex, also including local changes in pH and ion concentrations in cerebrospinal fluid, as well as migration and allosteric changes of neuronal membrane proteins (Yamada & Sumiyoshi, 2021; Chhabra et al, 2021; Dipasquale et al, 2017). Current studies mainly suggest that the overall effect of tDCS is associated with changes in excitability and spontaneous discharge rates in the stimulation areas (Nitsche & Paulus, 2000; Philip et al, 2017), as well as cross‐synaptic activation in interconnected remote areas (Chib et al, 2013), with side effects being ignored (Bikson et al, 2016).…”
Section: Introductionmentioning
confidence: 99%